Surface Treatment of Zirconia Implant, Its Surface Roughness and Its Effect on Osseointegration - A Review - Meshramkar, Roseline; Shetty, Praveen; Nayak, Aishwarya; Anehosur, Gouri V. (International Journal of Innovative Research in Medical Science, 2019)
Zirconia implant treatment is currently overriding other prosthetic solutions in replacing anterior teeth in esthetic zone. Surface topography of biomaterial has major impact on osseointegration. Various chemical and physical modifications have been developed to improve osseointegration. This review focuses on different surface treatment of zirconia implant. Surface roughness and its effect on osseointegration.